When I was Little Like You - Walsh, Jill Paton (Penguin Group, 1998)
Through a reflection of past experiences, a grandmother lovingly explains to her grandchild how things were different in the world when she was growing up.
Keywords: Family; Juvenile Fiction; Multigenerational